The Role of Brain-Derived Neurotrophic Factor (BDNF) in the Pathogenesis of Sarcopenia: A Meta-Analysis of Molecular Mechanisms - Susanto, Edi; Singgih Kusuma (HM Publisher, 2024)
Background: Brain-derived neurotrophic factor (BDNF), a neurotrophin crucial for neuronal survival and differentiation, has emerged as a potential key player in sarcopenia development. This meta-analysis aimed to systematically evaluate the molecular mechanisms by which BDNF contributes to sarcopenia. Methods: A comprehensive search of PubMed, Scopus, and Web of Science databases was conducted for studies published between 2018 and 2024 investigating the relationship between BDNF and sarcopenia at a molecular level. Studies were included if they met the following criteria: (1) examined BDNF signaling pathways in skeletal muscle; (2) assessed the impact of BDNF on muscle protein synthesis/degradation; (3) explored the role of BDNF in mitochondrial function and oxidative stress in muscle; and (4) investigated the influence of BDNF on muscle fiber type and neuromuscular junction integrity. Results: A total of 28 studies (n = 1,245 participants) met the inclusion criteria. The meta-analysis revealed that lower BDNF levels were significantly associated with: reduced muscle protein synthesis (SMD = -0.85, 95% CI: -1.12 to -0.58, p < 0.001); increased muscle protein degradation (SMD = 0.62, 95% CI: 0.35 to 0.89, p < 0.001); impaired mitochondrial function (SMD = -0.71, 95% CI: -0.98 to -0.44, p < 0.001); increased oxidative stress (SMD = 0.55, 95% CI: 0.28 to 0.82, p < 0.001); a shift towards fast-twitch muscle fibers (SMD = 0.48, 95% CI: 0.21 to 0.75, p = 0.001); and compromised neuromuscular junction integrity (SMD = -0.92, 95% CI: -1.21 to -0.63, p < 0.001). Conclusion: This meta-analysis provides compelling evidence that BDNF plays a pivotal role in the pathogenesis of sarcopenia through its multifaceted effects on muscle protein metabolism, mitochondrial function, oxidative stress, fiber type composition, and neuromuscular junction integrity.